On the limitation of Woo's algorithm for computing visibility maps. (2nd January 2016) - Li, Weishi
Abstract : The visibility map of a surface is a set of points on a unit sphere representing the directions along which all points on the surface in question are not occluded by itself, and it is long considered to be the dual of the Gauss map of the surface. In this paper, we consider the limitation of the algorithm proposed by Woo et al. for computing visibility maps. We show that the result cannot reflect the visibility of the surface correctly in some cases, in the sense that a direction along which the surface is occluded by itself may be contained in the visibility map computed using the algorithm. We give a condition for the occurrence of such cases with consideration of the projection of the boundary of the surface along the viewing direction.